(3EbJUGOjGJ GdYed (B/s - (3EjQfHQL, QhfGdOs; (3Q(B.(3SejK, QhHQJs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1994)
(3fXQI TGedI Ydi Shb GdYed, GdWdH Ydi GdYed, eQhfGJ GdWdH Ydi GdYed GeJOGOJ fXQjI GdWdH, GdYQV Gdcdj ddYed, GdCfJGL GdefRdj hGdCSQI, GdaQhb GdJYhjVjI ddCLhQ hCShGb GdYed, GdESJKeGQ aj QCS GdeGd GdHTQj, GdJYdje hGdJOQjH, GfJbGd GdYeGd Hjf GdhXGFa hGdgLQI GdEbdjejI, ehVhYGJ EbJUGOjI aj GdJYhjV, EJMGOGJ GdYeGd hGdeSGheI GdLeGYjI aj GdbWGY GdNGU, CShGb GdYed ddbWGY GdYGe, GdHWGdIs
Keywords: (3EbJUGOjGJ GdYeds; (3GdESJKeGQs; (3GdYeds